Analisis Kualitas Buku Teks Biologi Kelas XII Pada Materi Metabolisme Sel Berdasarkan Keterampilan Abad 21 - Nur Syahid (Jurnal Pendidikan Biologi Undiksha, 2023)
Revolution 4.0 created reforms in various fields, including education. Skill-based learning of the 21st century which contains aspects of 4C (Critical thinking, Creative thinking, Collaboration, Communication) emerged as a demand for the 4.0 revolution era in the field of education. The quality of textbooks greatly influences learning activities, therefore the quality of textbooks used must be in accordance with the curriculum and the development of science. This study aims to analyze the quality level of class XII biology textbooks on cell metabolism material based on aspects of 21st century skills. This study used a qualitative approach with content or document analysis methods. The instrument used in this study was in the form of a checklist containing the 4C aspect score (Critical thinking, Creative thinking, Collaboration, Communication). The results of the analysis show that book I (Erlangga) gets 17 scores out of 30 maximum scores with an average score of 1.70. Book II (Grafindo) obtained 25 scores out of 30 with a maximum score with an average score of 2.50. Book III (Yrama widya) obtained 29 scores out of 30 maximum scores with an average score of 2.90. Based on the results of the analysis, it was concluded that book I (Erlangga) had a fairly good quality, while book II (Grafindo) and book III (Yrama widya) had very good quality. The results of this study are expected to be a reference for teachers and schools to be more selective in choosing the textbooks used and to be a concern for writers and publishers to pay more attention to the quality of the books published.